Analisis Pengaruh Penggunaan Media Kahoot Terhadap Motivasi Belajar Siswa Di SMP Muhammadiyah 1 Surabaya - Hayati, Nur (Universitas Muhammadiyah Surabaya, 2024)
Mathematics learning is often considered complex, requiring strategies to enhance students' motivation and understanding. Technology-based learning media, such as Kahoot, offers a promising solution. This study aims to analyze the impact of using Kahoot on students' learning motivation at SMP Muhammadiyah 1 Surabaya. Using a qualitative method, data were collected through observation, interviews, and documentation. The results show that Kahoot increases students' enthusiasm and engagement in learning, creates an enjoyable learning atmosphere, and strengthens interactions between students and teachers. However, challenges such as device limitations and internet stability were identified. This study concludes that Kahoot is an effective interactive learning medium that can boost students' learning motivation when supported by adequate infrastructure. Keywords: Kahoot, Learning Motivation, Mathematics Learning, Educational Technology, Interactive Media